Development and Characterization of a Three-Dimensional Organotypic Human Vaginal Epithelial Cell Model(1) - Hjelm, Brooke E. (Biol Reprod, 2010)
We have developed an in vitro human vaginal epithelial cell (EC) model using the innovative rotating wall vessel (RWV) bioreactor technology that recapitulates in vivo structural and functional properties, including a stratified squamous epithelium with microvilli, tight junctions, microfolds, and mucus. This three-dimensional (3-D) vaginal model provides a platform for high-throughput toxicity testing of candidate microbicides targeted to combat sexually transmitted infections, effectively complementing and extending existing testing systems such as surgical explants or animal models. Vaginal ECs were grown on porous, collagen-coated microcarrier beads in a rotating, low fluid-shear environment; use of RWV bioreactor technology generated 3-D vaginal EC aggregates. Immunofluorescence and scanning and transmission electron microscopy confirmed differentiation and polarization of the 3-D EC aggregates among multiple cell layers and identified ultrastructural features important for nutrient absorption, cell-cell interactions, and pathogen defense. After treatment with a variety of toll-like receptor (TLR) agonists, cytokine production was quantified by cytometric bead array, confirming that TLRs 2, 3, 5, and 6 were expressed and functional. The 3-D vaginal aggregates were more resistant to nonoxynol-9 (N-9), a contraceptive and previous microbicide candidate, when compared to two-dimensional monolayers of the same cell line. A dose-dependent production of tumor necrosis factor-related apoptosis-inducing ligand and interleukin-1 receptor antagonist, biomarkers of cervicovaginal inflammation, correlated to microbicide toxicity in the 3-D model following N-9 treatment. These results indicate that this 3-D vaginal model could be used as a complementary tool for screening microbicide compounds for safety and efficacy, thus improving success in clinical trials.